Epidemiology of Leptospirainterrogans Serovar Hardjo Infection in Cattle - Bejo, Siti Khairani (2001)
The serological prevalence of Leptospira interrogans serovar hardjo (hereafter referred to serovar hardjo) infection in cattle in this present study was 30%. Water samples from stagnant water, pond water, tank water and drain water collected from the farms were positive to Leptospira biflexa (40%) . Twentyfour per cent of soil samples obtained from three different types of soil namely clay, loam and sand in the farms were also positive to Leptospira biflexa. However, serovar hardjo or other pathogenic leptospires were not isolated in the urine, soil and water samples collected in the farms. Clinical sign of leptospiral infection was not observed in the cattle on the farms. The leptospiral isolates were further characterized using bacterial restriction endonuclease DNA analysis (BRENDA), polyacrylamide gel electrophoresis (PAGE) and Western blotting. It was confirmed that the leptospiral isolates did not belong to serovar hardjo.Under experimental condition it was demonstrated that cattle are able to maintain serovar hardjo. Six female 8-months-old Kedah-Kelantan calves were used in this trial. Leptospiremia occurred as early as 7 days post-inoculation and lasted for 13 days following intra-conjunctival inoculation. Antibody against serovar lzardjo was first detected at day 7 post inoculation, then raised to a high level at day 14 post-inoculation and maintained at the same level up to 365 days post inoculation. Leptospiruria was first detected on day 49 post inoculation and maintained up to day 147 post-inoculation. Histologically serovar hardjo was detected in the renal tubule at the end of the trial using immunoperoxidase staining. No clinical signs of leptospiral infection was observed in the same animals throughout the trial. Identification of the leptospiral isolates obtained from the inoculum and urine samples of the experimental animals using bacterial restriction endonuclease DNA analysis (BRENDA) and polymerase chain reaction (peR) showed that both isolates were serovar hardjo. The study showed that serovar hardjo can survive in rain water up to 264 hours (11 days) under experimental condition. Leptospira interrogans serovar hardjo can survive up to 72 hours (3days) in diluted urine in Malaysian field condition and up to 984 hours (41 days) at 4°C. Leptospira interrogans serovar hardjo can survive in chlorinated drinking water up to 120 hours (5 days) but was killed immediately in seawater. The organism can survive in soil samples up to 144 hours (6 days) . The contaminated environment with serovar 11l1rdjo can transmit infection of the organism to susceptible animals. It is evident that serovar hardjo infection is present in cattle farms in Malaysia. Cattle in Malaysia have a potential of maintaining serovar hardjo. Leptospira interrogans serovar hardjo has been shown to survive in water and soil for a long time in Malaysian field condition and the organisms can be transmitted to susceptible animals.